The Effect of Variable Parameters on Carbon Residue of Iraqi Vacuum Gas Oil using Ultrasound Techniques - Abbas, Fatima H.; Naife, Tariq M.; Barghash, Hind (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
An ultrasonic treatment was applied to the vacuum gas oil at intervals of 5 to 30 minutes, at 70°C. In this work, the improvement of the important properties of Iraqi vacuum gas oil, such as carbon residue, was studied with several parameter conditions that affect vacuum efficiency, such as sonication time (5, 10, 15, 20, 25, and 30) min, power amplitude (10–50%). After ultrasonic treatment, the carbon residue of vacuum gas oil was evaluated using a Conradson carbon residue meter (ASTM D189). The experiment revealed that the oil’s carbon residue had decreased by 16%. As a consequence of the experiment It was discovered that ultrasonic treatment might reduce the carbon residual and density of oil samples being studied. It also noticed that the carbon residue reduced with increased ultrasonic treatment duration and power. The mechanical mixing and cavitation brought about by ultrasonic processing led to a number of modifications in the gas oil molecules. The properties of a typical molecular structure were altered on a microscale.